Nutrients content from new fallen leaves of teak from different sites - Haryono Supriyono; Daryono Prehaten (Jurnal Ilmu Kehutanan)
Litter on forest floor plays a very important role to maintain forest productivity and sustainability. The litter can control soil erosion, hydrology and nutrient cycles and has a function as carbon storage. The nutrients content in the leaf litter is affected by species, genetic, parent material, soil and climate. The objective of this research was to investigate the nutrient content of C, N, P, K, Ca, Mg, Na, Fe, Mn, and Cu in the litter from different sites. The newly fallen leaves samples were taken from the clonal teak plantation at ten years old, which planted at seven different sites in Java. The carbon (C) analysis was done with Walkley and Black and N with Kjeldahl method. Meanwhile for total P, K, Ca, Mg, Na, Fe, Mn, and Cu, the samples were extracted with mixture between HClO4 and HNO3, extracted P was measured with spectrophotometer and the metals of K, Ca, Mg, Na, Fe, Mn, and Cu were measured with Atomic Absorption Spectroscopy (AAS). The result showed that carbon content was not much different, valued 46.49-52.32%, and N and P had a little bit different value 0.52-1.28% and 0.04-0.14%, respectively. K, Ca, and Mg content was slightly different valued 0.06-0.52%, 1.69-2.64%, and 0.10-0.45%, respectively, while Na almost had not different ranged between 0.018-0.025%. Fe and Mn content were much different among the sites ranged 185-898 ppm and 63-202 ppm, respectively, while Cu and Zn were not much different valued 54-126 ppm and 32-58 ppm, respectively. The relationship between levels of elements that are mobile (C, N, and P) on litter and soil do not indicate a real trend. Otherwise immobile elements (K, Ca, Mg, and Na) are always consistent between the levels of nutrients in the litter with high levels of nutrients in the soil.